Seeking Inclusion In the 'Land of Broken Toys': Negotiating Mental Health Managerialism Among Homeless Men and Women - Dej, Erin Theresa (Université d'Ottawa / University of Ottawa, 2016)
Mental health, homelessness, addiction, and criminalization are the usual suspects of exclusion. The connection between these factors are often taken for granted, with positivistic accounts of causality making up the bulk of the literature. Using an institutional ethnography framework, this study draws attention to how individuals make sense of their exclusion. In particular, in this research I examine how homeless men and women ‘do’ their mental health status. Exploring themes of responsibilization, exclusion, identity, performativity, hope, and resistance, this research highlights the ways in which homeless individuals use the mental health system and the mental illness identity to contextualize their circumstances and to demonstrate their redeemability. Stemming from thirty-eight interviews with homeless men and women, participant observation, as well as a focus group with professionals and para-professionals I consider how mental illness identities are negotiated and performed among homeless men and women. Specifically, I am interested in how homeless individuals engage with mental health managerialism, given their vulnerable status. I contend that while some individuals resist mental illness discourses to varying degrees, a number of homeless individuals adopt the role of mental health consumer so as to align with the broader consumer society. In so doing, many homeless men and women seek to position themselves as included among the excluded and thus privy to the sense of hope, empowerment, and privileges that follow.
Keywords: Homelessness; Mental health; Exclusion; Governing through Freedom